The regulation of pharmaceuticals : balancing the benefits and risks - Grabowski, Henry G.; Vernon, John M. (Washington : American Enterprise Institute for Public Policy Research, 1983)
The book reviews the empirical evidence concerning the FDA's effect on the rate of innovation, the delays in introducing new drugs in the United States compared with Great Britain and other countries, the profitability of pharmaceutical research, and the reduction of risk to patients resulting from regulation.
Inludes bibliographical references.
oif 04/08/16
Loan
Keywords: Drugs; Pharmacy; Drug industry; Drugs; Legislation, Drug; Research; United States of America